A pilot randomized controlled trial of liraglutide 3.0 mg for binge eating disorder - Kelly C. Allison; Ariana M. Chao; Maija B. Bruzas; Courtney McCuen‐Wurst; Elizabeth Jones; Cooper McAllister; Kathryn Gruber; Robert I. Berkowitz; Thomas A. Wadden; Jena S. Tronieri (Wiley, 2023)
Abstract Objective To assess the efficacy of liraglutide 3.0 mg, a glucagon‐like peptide‐1 (GLP‐1) receptor agonist, for binge eating disorder (BED). Methods Adults with a body mass index (BMI) ≥ 27 kg/m2 enrolled in a pilot, 17‐week double‐blind, randomized controlled trial of liraglutide 3.0 mg/day for BED. The primary outcome was number of objective binge episodes (OBEs)/week. Binge remission, weight change, and psychosocial variables were secondary outcomes. Mixed effect models were used for continuous variables, and generalized estimating equations were used for remission rates. Results Participants (n = 27) were 44.2 ± 10.6 years; BMI = 37.9 ± 11.8 kg/m2; 63% women; and 59% White and 41% Black. At baseline, the liraglutide group (n = 13) reported 4.7 ± 0.7 OBEs/week, compared with 3.0 ± 0.7 OBEs/week for the placebo group, p = 0.07. At week 17, OBEs/week decreased by 4.0 ± 0.6 in liraglutide participants and by 2.5 ± 0.5 in placebo participants (p = 0.37, mean difference = 1.2, 95% confidence interval 1.3, 2.0). BED remission rates of 44% and 36%, respectively, did not differ. Percent weight loss was significantly greater in the liraglutide versus the placebo group (5.2 ± 1.0% vs. 0.9 ± 0.7%, p = 0.005). Conclusion Participants in both groups reported reductions in OBEs, with the liraglutide group showing clinically meaningful weight loss. A pharmacy medication dispensing error was a significant limitation of this study. Further research on liraglutide and other GLP‐1 agonists for BED is warranted.